Characteristic tetraspanin expression patterns mark various tissues during early Xenopus development. (24th January 2023) - Kuriyama, Sei; Tanaka, Masamitsu
Abstract: The tetraspanins (Tspans) constitute a family of cell surface proteins with four transmembrane domains. Tspans have been found on the plasma membrane and on exosomes of various organelles. Reports on the function of Tspans during the early development of Xenopus have mainly focused on the expression of uroplakins in gametes. Although the roles of extracellular vesicles (EVs) including exosomes have been actively analyzed in cancer research, the contribution of EVs to early development is not well understood. This is because the diffusivity of EVs is not compatible with a very strict developmental process. In this study, we analyzed members of the Tspan family in early development of Xenopus . Expression was prominent in specific organs such as the notochord, eye, cranial neural crest cells (CNCs), trunk neural crest cells, placodes, and somites. We overexpressed several combinations of Tspans in CNCs in vitro and in vivo. Changing the partner changed the distribution of fluorescent‐labeled Tspans. Therefore, it is suggested that expression of multiple Tspans in a particular tissue might produce heterogeneity of intercellular communication, which has not yet been recognized. Abstract : Several members of tetraspanins are now well‐known exosomal markers, however, the other members are not well analyzed. We tested tetraspanins' expression patterns during Xenopus development and found that they are prominently expressed in specific organs. Intercellular communication through extracellular vesicles has only just begun to be analyzed.